IDENTIFYING A PREDICTABLE PROPERTY CRIME TREND MODEL IN THE NORTH EAST OF ENGLAND - PITT, MARK,WILLIAM (2010)
This research examines the association of property crime sub-groups at police force district or basic command unit level, using official monthly police statistics and official claimant count (unemployment) data. The research focused on the region of the North East of England, encompassing the police force areas of Cleveland, Northumbria and Durham. The research used a post National Crime Recording Standards, (NCRS) sampling period, (April 2002 to March 2008) inclusive. The results based upon monthly time series data suggest that crime data is indeed integrated to the order one or I(1) and that there exists a co-integrating relationship between a number of property crime sub-groups, claimant counts and related crime sub-groups. The results suggest that the geographical area type has an influence on crime modelling. The research also gives an indication that further research may be warranted in the areas of crime substitution and crime recording practices at a sub-police force level. This research was supported by Cleveland Police and the National Police College Bramshill Fellowship Programme